Pemanfaatan Lingkungan Sekolah sebagai Sumber Belajar IPA-Biologi - GH, Muliana (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to explore the utilization of the school environment as a source of learning for Biology Science. The research method employed is qualitative research. Data collection techniques include interviews and distributing questionnaires. The research subjects are teachers at MTS Arifah Gowa. The findings of this research indicate that the use and utilization of the school environment as a source of learning for Biology Science are still limited among teachers. The study also reveals that there are various plants in the surroundings of MTS Arifah Gowa, representing gymnosperms, angiosperms encompassing dicotyledonous and monocotyledonous plants, pteridophytes, and bryophytes. Utilizing the school environment as a source of learning for Biology Science can provide direct learning experiences, active learning, and meaningful learning for students. The results of this research are expected to motivate teachers to develop methods and learning strategies that make better use of the school environment and its surroundings as a living laboratory and a learning resource in the subject of Science.